Facing a new pest : the case of the invasive fruit fly Drosophila suzukii in southern Sweden - Mühlhäuser, Emilia (SLU/Dept. of People and Society, 2017)
In an increasingly globalized food system, pests move easily together with food products and can cause significant damage in their new ranges. The problem is aggravated by climate change, enabling pest survival in previously uninhabitable areas. The fruit fly Drosophila suzukii Matsumura (Diptera: Drosophilidae) is a pest that has expanded its range to nearly global presence in the matter of a few years. Unlike most drosophilids, females of D. suzukii prefer to lay their eggs in fresh and ripening fruit, and this highly polyphagous fly has been very harmful to the soft fruit and berry industry globally. D. suzukii was first found in Sweden in 2014. Since then, it has been found in several soft fruit and berry crops but has not yet caused any significant economical damage. A group collaborating to deal with the fly has been started, including the Swedish Board of Agriculture (JBV), the Swedish University of Agricultural Sciences (SLU) and HIR, an independent agricultural advisory service company. This thesis describes the current situation from the perspectives of these actors and the growers, and the interactions between them. The possibilities to and potential benefits of increasing grower participation in the further work were analyzed. Focus lay on growers in Skåne, the southernmost region in Sweden. One method being developed for D. suzukii management is attract-and-kill using the substance SPLAT (specialized pheromone and lure application technology). D. suzukii is closely associated with the yeast species Hanseniaspora uvarum, and it was tested if the attractiveness of SPLAT could be improved using this yeast. A mixed methods approach was used, including semi-structured interviews, a growers’ survey and laboratory experiments. The analysis of data was pragmatic, and conducted within the frame provided by systems thinking. The inquiry showed that the response to the arrival of D. suzukii in Sweden has been satisfactory for all involved. For Skåne growers, D. suzukii is still a largely intangible and therefore not prioritized pest. Still, the outreach on D. suzukii has had a positive effect on grower awareness and practice. Skåne growers emerged as a highly heterogeneous group, including in their perception of D. suzukii as a threat. Small- and medium size growers were suggested by the survey results to be the most concerned about D. suzukii. Therefore, these growers are proposed to be prioritized when increasing grower participation, with Participatory action research (PAR) as a suggested working mode. A grower reference group collaborating with JBV, SLU and HIR could be a suitable point of entry for a PAR process, which could adress both socio-economical and IPM aspects of D. suzukii. As H. uvarum showed potential to improve the attractiveness of SPLAT for D. suzukii females, trying out new SPLAT formulas with this yeast under field conditions could be one activity of a future PAR group.